Invisible but Valuable: Unveiling the Accounting Potential from Malang City as a Communal Intangible Asset - Sopanah, Ana; Harnovinsah, Harnovinsah; Novianti, Indana Jamila; Rossalia, Kusila Meyrin (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Objectives: This study aims to examine the accounting recognition of Bantengan art as an intangible asset and to analyze its economic impact on enhancing local economic value. Methods: Using a qualitative approach and case study analysis of two Bantengan communities in Batu City, the study finds that accounting recognition is not carried out formally, but is realized through social accountability practices based on mutual cooperation, deliberation, and participatory transparency. Results: Five key findings related to accounting recognition include: the absence of formal financial records, the dominance of cultural values over economic ones, gotong royong as a form of social control, resistance to the institutionalization of formal accounting, and the need for a value- and narrative-based accounting approach. Meanwhile, the economic impacts of Bantengan recognition include: increased attractiveness of cultural tourism, growth of the local creative economy sector, community involvement in collective economic activities, expanded access to funding and CSR, and strengthened community economic identity. Implications: The study concludes that a contextual, community-based accounting approach can holistically represent cultural values and integrate Bantengan as a strategic asset in inclusive and sustainable local economic development.